L-selenomethionine inhibits small intestinal ferroptosis caused by ammonia exposure through regulating ROS-mediated iron metabolism - Xinxin Zhang; Lepeng Gu; Ying Chen; Tianqi Wang; Houjuan Xing (Ecotoxicology and Environmental Safety)
Ammonia is an important component of PM2.5 and PM10, and is also a major harmful gas in intensive and large-scale pig houses, which poses a potential threat to the health of farmers and animals. Intestinal tract is the largest immune organ in the body and is also an important target organ for ammonia exposure. However, the potential toxicity mechanism of ammonia exposure to the intestine remains unclear. L-selenomethionine is an important source of organic selenium with the advantages of high bioavailability, safety and high efficiency. In order to explore the mechanism of ammonia enterotoxicity and the mitigation effect of L-selenomethionine on ammonia enterotoxicity, multi-dimensional ammonia toxicity models and L-selenomethionine intervention models were established in vivo and in vitro. The results showed that ammonia exposure up-regulated the levels of iron, ROS, MDA, and LPO in the small intestinal tissue and the IPEC-J2 cell, down-regulated the activities of antioxidant enzymes and the content of GSH, inhibited the Nrf2 pathway, significantly altered the expression of ferroptosis (TFR-1, FPN-1, FTH1, SLC7A11, GPX4, ACSL4) and intestine tight junctions (Claudin-1, Occludin, ZO-1) genes. Compared with the ammonia exposure group, L-selenomethionine group could significantly improve the changes of these ferroptosis indicators by affecting ROS and iron levels through Nrf2 pathway. Our results indicated that L-selenomethionine inhibited small intestinal epithelial cells ferroptosis caused by ammonia exposure through regulating ROS-mediated iron metabolism.